The function and word order of particles »zajisté« (certainly) and »pak« (then) in Old and Middle Czech - Ježová, Martina (Bohemistyka, 2023)
The paper focuses on Latin influence on the properties of the Old and Middle Czech lexical items zajisté and pak. According to the previous diachronic syntactic studies, these expressions were able to copy the word order of some Latin particles and extract constituents of nominal phrase in Old Czech, i. e. follow the typically Latin word order pattern (see Navrátilová 2017, 2018). The aim is to introduce their functions and the developement of their word order in Old and Middle Czech in comparison with the properties of their Latin equivalents. The analysis is based on the data excerpted from the corpora of Old and Middle Czech texts (Staročeská textová banka, Středněčeská textová banka) and from biblical text of the Gospel of Luke in four translations representing various stages of older Czech (Olomouc Bible, Miller’s Bible, Melantrich’s Bible, St. Wenceslas Bible) and in their Latin pretext (Vulgate).